Roles of Reactive Oxygen Species in the Spermatogenesis Regulation - Guerriero, Giulia; Trocchia, Samantha; Abdel-Gawad, Fagr K.; Ciarcia, Gaetano (Frontiers in Endocrinology, 2014)
Spermatogenesis is a complex process of male germ cells proliferation and maturation from diploid spermatogonia, through meiosis, to mature haploid spermatozoa. The process involves dynamic interactions between the developing germ cells and their supporting Sertoli cells. The gonadal tissue, with abundance of highly unsaturated fatty acids, high rates of cell division and variety of testis enzymes results very vulnerable to the overexpression of reactive oxygen species (ROS). In order to address this risk, testis has developed a sophisticated array of antioxidant systems comprising both enzymes and free radical scavengers. This chapter sets out the major pathways of testis generation, the metabolism of ROS and highlights the transcriptional regulation by steroid receptors of antioxidant stress enzymes and their functional implications. It also deals with of the advantages of the system biology for an antioxidant under steroid control, the major seleno protein expressed by germ cells in the testis, the phospholipid hydroperoxide glutathione peroxidase (PHGPx/GPx4) having multiple functions and representing the pivotal link between selenium, sperm quality and specie preservation.